2008
DOI: 10.1152/japplphysiol.00025.2008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hemoglobin oxygen saturation using Raman microspectroscopy and 532-nm excitation

Abstract: The resonant Raman enhancement of hemoglobin (Hb) in the Q band region allows simultaneous identification of oxy- and deoxy-Hb. The heme vibrational bands are well known at 532 nm, but the technique has never been used to determine microvascular Hb oxygen saturation (So(2)) in vivo. We implemented a system for in vivo noninvasive measurements of So(2). A laser light was focused onto areas of 15-30 microm in diameter. Using a microscope coupled to a spectrometer and a cooled detector, Raman spectra were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 50 publications
5
50
0
1
Order By: Relevance
“…It is to be mentioned that the degree of oxygenation (SO 2 ) can be expressed as SO 2 ¼ A × PR þ B, where A and B are the constants characterizing the conditions of the process; the details are mentioned elsewhere. 37 From Fig. 7, it also can be seen that some delay of the oxygenation of deoxygenated RBC is observed at the presence of cND, this delay being more significant for 5 nm cND and deeper deoxygenation.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…It is to be mentioned that the degree of oxygenation (SO 2 ) can be expressed as SO 2 ¼ A × PR þ B, where A and B are the constants characterizing the conditions of the process; the details are mentioned elsewhere. 37 From Fig. 7, it also can be seen that some delay of the oxygenation of deoxygenated RBC is observed at the presence of cND, this delay being more significant for 5 nm cND and deeper deoxygenation.…”
Section: Resultsmentioning
confidence: 79%
“…6, the oxygenation-deoxygenation cycle of RBC and RBC interacting with cND is characterized using the intensity ratio of peaks for oxygenated state at 1588 cm −1 , and for deoxygenated state at 1555 cm −1 (attributed as ν 19 or ν 37 ). 37 The dependencies of the peak ratio ½PR ¼ I 1588 ∕ðI 1555 þ I 1588 Þ on time, during deoxygenation followed by re-oxygenation, are presented in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…The scattered light was captured in the charged-coupled spectrometer each second, producing different spectral peaks linearly proportional to oxy- and deoxyhemoglobin concentrations. These peaks were converted to a ratio of oxyhemoglobin to total hemoglobin by averaging data from 20 to 180 individual spectra [11,17,18,19]. The first 5 min of data were excluded to allow skin surface adequate time to “auto-fluoresce” to diminish signal-to-noise ratio.…”
Section: Methodsmentioning
confidence: 99%
“…225,226 It was later shown that this approach was highly sensitive to an individual's peripheral microcirculation 227,228 and the test subject's hemoglobin concentration. 229 Much of the early work on the in vivo analysis of hemoglobin oxygenation for surgical applications was carried out by Torres Filho et al They reported the utility of UV-RRS for the simultaneous identifications of oxyhemoglobin and deoxyhemoglobin in the microvessels of a living rat using a single excitation wavelength (406.5 nm in one study, 230 and 532 nm in another 231 ). When the rat's hemoglobin saturation (as measured by a commercial oximeter) was <1% (deoxygenated) or >98% (oxygenated), a single Raman peak was observed.…”
Section: In Vivo Raman Spectroscopic Analysis Of Bloodmentioning
confidence: 99%